A preliminary study of the effect of a high-salt diet on transcriptome dynamics in rat hypothalamic forebrain and brainstem cardiovascular control centers - Ramachandran, Chitra Devi; Gholami, Khadijeh; Lam, Sau Kuen; Hoe, See Ziau (PeerJ, 2020)
Background High dietary salt intake is strongly correlated with cardiovascular (CV) diseases and it is regarded as a major risk factor associated with the pathogenesis of hypertension. The CV control centres in the brainstem (the nucleus tractus solitarii (NTS) and the rostral ventrolateral medulla (RVLM)) and hypothalamic forebrain (the subfornical organ, SFO; the supraoptic nucleus, SON and the paraventricular nucleus, PVN) have critical roles in regulating CV autonomic motor outflows, and thus maintaining blood pressure (BP). Growing evidence has implicated autonomic regulatory networks in salt-sensitive HPN (SSH), but the genetic basis remains to be delineated. We hypothesized that the development and/ or maintenance of SSH is reliant on the change in the expression of genes in brain regions controlling the CV system. Methodology We used RNA-Sequencing (RNA-Seq) to describe the differential expression of genes in SFO, SON, PVN, NTS and RVLM of rats being chronically fed with high-salt (HS) diet. Subsequently, a selection of putatively regulated genes was validated with quantitative reverse transcription polymerase chain reaction (qRT-PCR) in both Spontaneously Hypertensive rats (SHRs) and Wistar Kyoto (WKY) rats. Results The findings enabled us to identify number of differentially expressed genes in SFO, SON, PVN, NTS and RVLM; that are either up-regulated in both strains of rats (SON- Caprin2, Sctr), down-regulated in both strains of rats (PVN- Orc, Gkap1), up-regulated only in SHRs (SFO- Apopt1, Lin52, AVP, OXT; SON- AVP, OXT; PVN- Caprin2, Sclt; RVLM- A4galt, Slc29a4, Cmc1) or down-regulated only in SHRs (SON- Ndufaf2, Kcnv1; PVN- Pi4k2a; NTS- Snrpd2l, Ankrd29, St6galnac6, Rnf157, Iglon5, Csrnp3, Rprd1a; RVLM- Ttr, Faim). Conclusions These findings demonstrated the adverse effects of HS diet on BP, which may be mediated via modulating the signaling systems in CV centers in the hypothalamic forebrain and brainstem.
Keywords: High-salt diet; Nucleus tractus solitarii (NTS); Hypertension; Subfornical organ (SFO); Rostral ventrolateral medulla (RVLM); Paraventricular nucleus (PVN); Supraoptic nuclei (SON)